Exploring the educational factors affecting health and food literacies in Korean diabetes care - Nam, Young Hee (Edelweiss Applied Science and Technology, 2025)
This research sought to enhance the overall well-being and nutritional practices of individuals with diabetes by pinpointing the determinants that affect their comprehension of health and food information. The data were analyzed using SPSS 26.0. The experienced group received diabetes management instruction, with 11% more men than women. Compared to the non-educated group, individuals who received training were generally younger, had attained higher education levels, and more frequently maintained a partner relationship or exhibited a higher BMI. The experienced group excelled in reading comprehension of nutrition labels and food literacy, while those without such training encountered greater challenges. Educational interventions in diabetes care were positively associated with improvements in food literacy, health literacy, and the application of diverse treatment strategies. The investigation revealed that factors such as age, education level, occupation, prior weight management experience, and exposure to health and nutritional education—as well as the variety of diabetes treatment methods employed—significantly influenced patients’ educational experiences. Understanding health literacy was 1.295 times greater for diabetic patients, and understanding food literacy was 1.341 times greater. Implementing education and raising awareness can help diabetic patients manage their disease and prevent complications.